HUBUNGAN KEMANDIRIAN DAN PERSEPSI SISWA TENTANG KOMPETENSI GURU EKONOMI DENGAN KECAKAPAN HIDUP SISWA SMA KELAS XII IPS DI BANJARMASIN UTARA - Raihanah Sari (Universitas Lambung Mangkurat, 2016)
This research aimed to explain and to describe the Relation between Independence and Student’s perception about Economic Teacher’s Competence with Life Capability of Student’s. Survey method is the used in this study through questionnaire as data collection of 220 students which took randomly from each school grade of Social field in Senior High School in north Banjarmasin. The result of this research is aimed relation between independence and student’s perception about economic teacher’s competence with life capability of student’s. Keyword: kemandirian, persepsi siswa, kompetensi guru ekonomi, kecakapan hidup siswa